MODIFICATION OF NATURAL ZEOLITE FROM CIKALONG WEST JAVA WITH HEXADECIL TRIMETIL AMMONIA AND ABSORPTION RATE TEST OF SULPHATE AND CHROMATE IONS - Husaini Husaini; Trisna Soenara (Jurnal Zeolit Indonesia, 2003)
Cikalong mordenit natural zeolite with the average of cation exchange capacity (CEC) 154,2 meq/100 g has been used on modification trial. This modification attempts to increases the rate of anions absorbtion of zeolite in solution. On this research, zeolite is modificated using HDTMA through stirring process on beaker glass. Before the modification start, zeolite is set on pH 5 using sodium acetate solution. Variables on this research are: zeolite size ("“10+18 mesh, -18+28 mesh, and "“28+48 mesh), and HDTMA dosage (50%, 100%, and 200%). Furthermore modification of zeolite is tested it's suphaate and chromate ions absorbtion rate. The modification of zeolite showed that the range of HDTMA weight percent that covers the surface of zeolite is 4,21 "“ 13,49% with the range of exchange ion capacity rate 137,05 "“ 143,00 meq/100 g. The best result of the absorbtion rate test is the -28 + 48 mesh zeolite with HDTMA dosage 200% for 49,46 mg/100g (5,15 mmol/kg) sulphate and for the cromat ion on -10 + 18 mesh zeolite with 50% HDTMA dosage, the absorbtion rate is 61,05 mg/100g (6,36 mmol/kg).